2015
DOI: 10.1093/jjco/hyv082
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal function of patients with advanced urothelial cancer on eligibility for first-line chemotherapy and treatment outcomes

Abstract: Objective: The aim of the study is to clarify the clinical effects of first-line chemotherapy regimens for advanced urothelial cancer on clinical responses and survival of patients grouped by renal function. Methods: In this multicenter retrospective cohort study, 345 urothelial cancer patients received systemic chemotherapy for metastatic or unresectable disease in 17 centers . Results: Two hundred and forty-one patients were treated with methotrexate, vinblastine, doxorubicin and cisplatin/methotrexate, epir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Eighteen studies here 9 13 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 were used to estimate the prevalence of renal insufficiency in patients with UC ( Table 2 ). The prevalence of pre-operative renal insufficiency in UC in this systematic review was 35.9% (ranging from 11.9% to 75.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies here 9 13 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 were used to estimate the prevalence of renal insufficiency in patients with UC ( Table 2 ). The prevalence of pre-operative renal insufficiency in UC in this systematic review was 35.9% (ranging from 11.9% to 75.3%).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical utility of epirubicin is limited by its dose-dependent toxicity in tissues such as the heart, the liver and the kidney, which lead to reduced antitumor efficacy (Kebieche et al, 2009;Ichioka et al, 2015). Generally, the toxicity in the kidney was attributed to the functional properties of the kidney and the effective elimination of many antineoplastic drugs and their metabolites (Pan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness and the safety of cisplatin dose reduction in patients with pretreatment eGFR < 60 mL/ min/1.73 m 2 has not been clearly elucidated because of the ethical difficulties surrounding conducting such a prospective study [12,24]. Although the one-year overall survival of the patients treated with a reduced dose of cisplatin-based chemotherapy was significantly lower than that of those treated with the standard dose in the CURE study using the same patient series [13], the results of this study demonstrated the safety of cisplatin dose reduction for cisplatin-ineligible patients in preventing nephrotoxicity. Even considering our study results, cisplatin-based chemotherapy is not always safe and is not recommended for all the CKD-S patients with a solitaryfunctioning kidney with pretreatment eGFR < 60 mL/ min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes for cisplatin-eligible advanced UC patients treated with carboplatin-based chemotherapies, such as gemcitabine plus carboplatin, with a median overall survival of 9.0 months, were poorer than those for patients treated with cisplatin-based chemotherapies [6,7]. However, in cisplatin-ineligible advanced UC patients, the median overall survival of patients treated with carboplatin-based combination chemotherapies are reported 7.2-16.3 months [8][9][10][11], which is almost similar (i.e., around 10 months) in those treated with cisplatinbased chemotherapies, including the reduction of cisplatin [12,13] or a split dose of cisplatin regimens [14][15][16].…”
Section: Introductionmentioning
confidence: 90%